Genetic Diversity of Cucumber Mosaic Virus Strain Soybean from Several Areas - TRI ASMIRA DAMAYANTI; SURYO WIYONO (Microbiology Indonesia, 2015)
Cucumber mosaic virus strain soybean (CMV-S) is one of economically important virus infecting soybean in Indonesia. However, it is very few information related with the CMV-S Indonesia isolates. Thus, the aim of present work is to detect and identify CMV-S isolates from different origin. Leaf samples collected from six different soybean fields in Java and North Sumatera. Molecular detection was carried out by reverse transcription polymerase chain reaction (RT-PCR) using specific primer of the coat protein (CP) gene and DNA sequencing. RT-PCR were successfully amplified the entire CP gene size ~657 bp from all samples and encoded 218 amino acids. Analysis of nucleotide and amino acid sequences showed high homology among isolates ranging from 99.5% and 100%. However isolate from Sindang Laut either nucleotides or amino acids showed lower homology to that of five isolates ranging from 89.4%-89.6% and 91.7%, respectively. The differences between CMV-S with other non legume strain found in six amino acid positions in the CP gene, suggesting the differences might related with host specificity. Phylogenetic analysis of amino acid of six isolates to other CMV strain showed that the five CMV-S isolates were in the same cluster, while Sindang Laut isolate was in different cluster together with the non-legume CMV from India. It is indicating the present of genetic variability among CMV-S isolates in Java.